Light transmission through the material of composite scintillator - Karavaeva, N.L.; Martynenko, E.V.; Panikarskaya, V.D.; Tarasenko, O.A. (Functional Materials, 2012)
Single-layer and multilayer (20 mm high) composite scintillators based on stilbene were studied in the work. For all the scintillators the luminous transmittances on wavelengths of 360 nm, 390 nm, 440 nm and 700 nm have been measured. It was shown that the basic channel of light losses for investigated systems is not absorption by stilbene of its luminescence, but light scattering by grain boundaries. For the multilayer composite scintillators the scintillation response value increased with the grain size growth. This dependence is accounted for decrease of the amount of scattering facets on the path of light to a photodetector.